IMPLEMENTASI PROGRAM BILINGUAL DI MTS SALAFIYAH HIDAYATUL ATHFAL PEKALONGAN - Luqni Assaqaf Luqni; Muhdi; Endang Wuryandini (STKIP Subang, 2023)
Bilingual learning programs are aimed at promoting bilingualism by using the first language proportionally or using two languages ​​as the language of instruction for various subjects. The purpose of this research is to: describe and analyze the implementation of the Bilingual Program at MTs Salafiyah Hidayatul Athfal Pekalongan. The research approach used is qualitative. This type of research is a case study. Qualitative research design goes through three stages, namely: orientation, focused exploration, and data analysis. Data collection techniques are interviews, observation and documentation. This research uses source triangulation. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The results of the research show that: 1) planning for the implementation of the bilingual program is carried out using planning procedures including preparing madrasah administration, academic supervision programs, budgeting formulation, infrastructure planning, administration and plan evaluation. 2) Organizing the implementation of the bilingual program is carried out using organizational procedures including placement of madrasa resources, organizational planning and development, assignment and delegation of authority. 3) The drive for implementing the bilingual program is carried out by the madrasa head, including directing the madrasa head and motivating the madrasa head. 4) Supervision of the implementation of the bilingual program is carried out by the head of the madrasah including assessment instruments, evaluation of implementation activities, and follow-up. Conclusion: The implementation of the bilingual program has been carried out through two steps of activities, namely planning, organizing, mobilizing and supervising. The author suggests that madrasa heads pay more attention to mobilization and supervision. Teachers are required to always be ready to carry out activities.